Versatility of the supraclavicular pedicle flap in head and neck reconstruction - GIORDANO, L. (Acta Otorhinolaryngol Ital, 2014)
Head and neck surgery has witnessed an increase in microvascular reconstructive procedures with free flaps over the last 20 years as they offer efficient functional recovery. Nevertheless, under certain circumstances they may be contraindicated or cannot be used. We present the use of supraclavicular pedicled flap in three patients with different recipient sites. All patients had acceptable functional and aesthetic outcomes. Donor-site morbidity was satisfactory. Supraclavicular pedicled flap is not only an alternative to free flap reconstruction, but also a first-choice option in head and neck reconstructive surgery.